A macroprudential theory of foreign reserve accumulation - Fernando Arce; Julien Bengui; Javier Bianchi (Federal Reserve Bank of Chicago, 2022)
We propose a macroprudential theory of foreign reserve accumulation that can rationalize the secular trends in public and private international capital flows. In middle-income countries, the increase in international reserves has been associated with elevated private capital inflows, both in the aggregate and in the cross-section, and reserve holdings have been more prominent in economies with a more open capital account. We present an open economy model of financial crises that is consistent with these features. We show that the optimal reserve accumulation policy leans against the wind, raising gross private borrowing while improving the economy's net foreign asset position and reducing the exposure to financial crises.
Keywords: E58; F31; F32; F34; 330; Macroprudential policy; international reserves; financial crises; gross capital flows